Performance of Renewable Energy Auctions : Experience in Brazil, China and India - Elizondo Azuela, Gabriela (World Bank Group, Washington, DC, 2014)
This paper considers the design and performance of auction mechanisms used to deploy renewable energy in three emerging economies: Brazil, China, and India. The analysis focuses on the countries' experience in various dimensions, including price reductions, bidding dynamics, coordination with transmission planning, risk allocation strategies, and the issue of domestic content. Several countries have turned to public competitive bidding as a mechanism for developing the renewable generation sector in recent years, with the number of countries implementing some sort of auction procedure rising from nine in 2009 to 36 by the end of 2011 and about 43 in 2013. In general, the use of auctions makes sense when the contracting authority expects a large volume of potentially suitable bids, so that the gains from competition can offset the costs of implementation. A study of the successes and failures of the particular auction design schemes described in this paper can be instrumental in informing future policy making.